Large Economic Units, Banks, and the Transactions Demand for Money - Sprenkle, Case M. (Quarterly Journal of Economics, 1966)
Journal Article Large Economic Units, Banks, and The Transactions Demand for Money Get access Case M. Sprenkle Case M. Sprenkle University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 80, Issue 3, August 1966, Pages 436–442, https://doi.org/10.2307/1880729 Published: 01 August 1966